2023
DOI: 10.1167/tvst.12.6.2
|View full text |Cite
|
Sign up to set email alerts
|

Test–Retest Reliability of Virtual Reality Devices in Quantifying for Relative Afferent Pupillary Defect

Abstract: Background The swinging flashlight test (SFT) is one of the most prominent clinical tests for detecting the relative afferent pupillary defect (RAPD). A positive RAPD localizes the lesion to the affected afferent pupil pathway and is a critical part of any ophthalmic exam. Testing for an RAPD, however, can be challenging (especially when small), and there is significant intrarater and interrater variability. Methods Prior studies have shown that the pupillometer can imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The head-mounted device (including CS assessment) may also find future terrestrial applications to allow for more convenient, rapid, and frequent visual assessments, as well as for opportunities for at-home testing ( 17 ). Further research to establish test–retest reliability will also be essential when bringing this technology into the clinical setting ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…The head-mounted device (including CS assessment) may also find future terrestrial applications to allow for more convenient, rapid, and frequent visual assessments, as well as for opportunities for at-home testing ( 17 ). Further research to establish test–retest reliability will also be essential when bringing this technology into the clinical setting ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of virtual reality technology has revolutionized many fields, including sports and medicine [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Research in virtual reality has found that decision making in sub-elite soccer officials between on-field and virtual reality were indistinguishable, suggesting virtual reality offers a representative training environment [ 28 ].…”
Section: 3d Environment Virtual Reality Research For Football Officia...mentioning
confidence: 99%
“…Intraclass correlation (ICC) has long been recognized as a vital reliability and reproducibility metric, especially for gauging similarity in paired data when the order of pairing is not preserved [96,106,107]. In brain imaging, it serves as a popular baseline for test-retest (TRT) reliability assessments, often in conjunction with the Dice coefficient [108][109][110][111][112].…”
Section: Plos Computational Biologymentioning
confidence: 99%